Early, Late or Never? When Does Parental Education Impact Child Outcomes?. (7th December 2016) - Dickson, Matt; Gregg, Paul; Robinson, Harriet
Abstract : We estimate the causal effect of parents' education on their children's education and examine the timing of the impact. We identify the causal effect by exploiting the exogenous shift in (parents') education levels induced by the 1972 minimum school leaving age reform in England. Increasing parental education has a positive causal effect on children's outcomes that is evident in preschool assessments at age 4 and continues to be visible up to and including high‐stakes examinations taken at age 16. Children of parents affected by the reform attain results around 0.1 standard deviations higher than those whose parents were not impacted.